Prediction of Ki‐67 of Invasive Ductal Breast Cancer Based on Ultrasound Radiomics Nomogram. (19th July 2022) - Zhu, Yunpei; Dou, Yanping; Qin, Ling; Wang, Hui; Wen, Zhihong
Abstract : Purpose: The objective of this research was to develop and validate an ultrasound‐based radiomics nomogram for the pre‐operative assessment of Ki‐67 in breast cancer (BC). Materials and Methods: From December 2016 to December 2018, 515 patients with invasive ductal breast cancer who received two‐dimensional (2D) ultrasound and Ki‐67 examination were studied and analyzed retrospectively. The dataset was distributed at random into a training cohort (n = 360) and a test cohort (n = 155) in the ratio of 7:3. Each tumor region of interest was defined based on 2D ultrasound images and radiomics features were extracted. ANOVA, maximum correlation minimum redundancy (mRMR) algorithm, and minimum absolute shrinkage and selection operator (LASSO) were performed to pick features, and independent clinical predictors were integrated with radscore to construct the nomogram for predicting Ki‐67 index by univariate and multivariate logistic regression analysis. The performance and utility of the models were evaluated by plotting receiver operating characteristic (ROC) curves, decision curve analysis (DCA), and calibration curves. Results: In the testing cohort, the area under the receiver characteristic curve (AUC) of the nomogram was 0.770 (95% confidence interval, 0.690–0.860). In both cohorts, the nomogram outperformed both the clinical model and the radiomics model ( P  < .05 according to the DeLong test). The analysis of DCA proved that the model has clinical utility. Conclusions: The nomogram based on 2D ultrasound images offered an approach for predicting Ki‐67 in BC.